Motivación y desempeño laboral de los trabajadores de la Casa de las Enchiladas Iquitos 2025 - Flores Rios, Rita Milagro (2025)
The main purposes of this research were to establish the correlation between motivation and job performance of workers at Casa de las Enchiladas Iquitos 2025. The research was a quantitative approach based on the collection and subsequent statistical analysis of data, in addition to the descriptive and correlational level, since we sought to describe the current situation of workers and the relationship of the variables. The design was non-experimental and correlational cross-sectional, since the phenomena were observed at a specific time in which variables were not manipulated. The results obtained through the Spearman test gave a coefficient of 0.715 with significance p = 0.000, which proves that there is a positive, high and statistically significant correlation between motivation and job performance. That is, as motivation increases, so does performance, validating our alternative hypothesis. It is concluded that the increase in productivity is directly influenced by work motivation in addition to organizational objectives, being a key factor in strengthening the company's performance.